EDITORIAL. - DEIGH, JOHN (Ethics, 2008)
The article presents the editor's view on the trend toward electronic publication of scholarly journals. He also comments on his departure as editor of the journal and welcomes his successor, Henry Richardson. Also included is a pair of charts showing statistics regarding decisions on submitted manuscripts, and on origins of the manuscript authors.